An improved parallel archutecture for MPEG-4 motion estimation in 3G mobile applications - Xu, D; Gao, R; Batatia, H; IEEE; IEEE; IEEE (2003)
A high-parallel VLSI core architecture for MPEG-4 motion estimation is proposed in this paper. It possesses the characteristics of low memory bandwidth and low clock rate requirements, thus primarily aiming at 3G mobile applications. Based on a one-dimensional tree architecture, the architecture employs the dual-register/buffer technique to reduce the preload and alignment cycles. As an example, full-search block matching algorithm has been mapped onto this architecture using a 16-PE array that has the ability to calculate the motion vectors of QCIF video sequences in real time at 1 MHz clock rate and using 15.5 Mbytes/s memory bandwidth.